Interplay of Good Bacteria and Central Nervous System: Cognitive Aspects and Mechanistic Considerations - Salami, Mahmoud (Frontiers in Neuroscience, 2021)
ABSTRACT The human gastrointestinal tract hosts trillions of microorganisms that is called, "gut microbiota". The gut microbiota is involved in a wide variety of physiological features and functions of the body. Thus, it is not surprising that any damage to the gut microbiota is associated with disorders in different body systems. Probiotics, defined as living microorganisms with health benefits for the host, can support or restore the composition of the gut microbiota. Numerous investigations have proved a relationship between the gut microbiota with normal brain function as well as many brain diseases, in which cognitive dysfunction is a common clinical problem. On the other hand, increasing evidence suggests that the existence of a healthy gut microbiota is crucial for normal cognitive processing. In this regard, interplay of the gut microbiota and cognition has been under focus of recent researches. In the present paper I review findings of the studies considering beneficial effects of either gut microbiota or probiotic bacteria on the brain cognitive function in the healthy and disease statuses.